Diagnosis and Management of Peyronie’s Disease: A Clinical Consensus Statement and Recommendations from the Korean Society for Sexual Medicine and Andrology - Dong Soo Kim; Hee Jo Yang; Hyun Cheol Jeong; Ki Hyuck Moon; Dong Sup Lee; Seung Hun Song; Won Ki Lee (The World Journal of Men's Health)
Peyronie’s disease is an acquired condition characterized by penile deformities caused by fibrosis of the penile tunica albuginea, leading to symptoms such as penile pain, erectile dysfunction, and other associated issues. Despite extensive research, the pathophysiology of this condition remains poorly understood, and standardized diagnostic and treatment protocols are lacking. While clinical guidelines from several professional societies exist, they do not consistently account for factors such as patient ethnicity, geography, and socioeconomic status. Thus, the Korean Society for Sexual Medicine and Andrology (KSSMA) aimed to develop recommendations tailored to clinical practice in Korea. These recommendations summarize the latest evidence, including clinical practice guidelines from various international professional societies, and represent the consensus opinion of an expert group within the KSSMA. They encompass all aspects of Peyronie’s disease, including the definition, diagnosis, non-surgical interventions, and surgical treatment options.